2014
DOI: 10.4172/2167-7182.1000147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Program Requiring Attention, Memory and Imitation on Cognitive Function in Elderly Persons: A Non-Randomized Pilot Study

Abstract: Background: Square-Stepping Exercise (SSE) was developed as a novel exercise form that combines physical and cognitive training. Participants watch, recognize, memorize and follow step patterns which an instructor demonstrates on a 4 by 10 square-patterned SSE mat without viewing printed pattern diagrams. The purpose of this study was to examine the effects of SSE on cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…We did not measure EF in the current study, therefore it is unknown whether adverse changes in DT cycle time variability was associated with unfavorable changes in EF. Nonetheless, this assumption is unlikely given that SSE has been associated with improve EF in previous studies (Shigematsu, 2014;Teixeira et al, 2013). Rather, we argue that because of the above describe characteristics of the SSE program, increased gait variably would likely result from a more cautious gait pattern developed in response to performing stepping patterns requiring increased attention and concentration.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We did not measure EF in the current study, therefore it is unknown whether adverse changes in DT cycle time variability was associated with unfavorable changes in EF. Nonetheless, this assumption is unlikely given that SSE has been associated with improve EF in previous studies (Shigematsu, 2014;Teixeira et al, 2013). Rather, we argue that because of the above describe characteristics of the SSE program, increased gait variably would likely result from a more cautious gait pattern developed in response to performing stepping patterns requiring increased attention and concentration.…”
Section: Discussionmentioning
confidence: 82%
“…Looking at our findings from a neurological/cognitive perspective, it was also expected that SSE would improve DT gait parameters to a greater extent in the M4 group compared to the M2 group. Previous studies reported that SSE has been associated with improvements in EF subdomains (i.e., attention and mental flexibility) (Shigematsu, 2014;Teixeira et al, 2013), which are understood as primary cognitive functions and/or brain networks involved in DT gait functioning (Yogev-Seligmann et al, 2008). Therefore, it was believed that even though SSE is of lower physical intensity, it would enhance DT gait parameters by benefiting EF, via a more neurological/cognitive pathway as opposed to a neuromuscular pathway, due to its high cognitive demand.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Before starting the session, the first activity to be carried out will be to remember the last movement pattern executed in the previous session. Once the patients have memorized the pattern, which is expected to be achieved after 4-5 repetitions, based on a previous study [23], they will continue with the session autonomously. At the end of each session, they will contact the SSE expert who will ask them about the session development and will question them about two scales: The rating will be of perceived exertion [24] and level of pain, also recording any incident or problem during the training session.…”
Section: Experimental Group (Tele-sse)mentioning
confidence: 99%
“…Stepping Exercise (SSE) is a low-cost and easily administered group-based exercise intervention that involves replicating a previously demonstrated stepping pattern in order to progress across a gridded floor mat. Although SSE was originally designed and deemed effective for improving lower extremity functional fitness and reducing falls risk factors in high-risk elderly fallers (41), recent results suggest that SSE may improve cognition [i.e., memory, and EF (39), and global cognition, attention, and mental flexibility (45)]. The excellent long-term adherence to SSE (i.e., regular participation over a 4-year longitudinal follow-up) is driven by a number of factors, including the simplicity of the exercise program and the facilitation of the development of friendship and social communication between peers of similar age (40).…”
Section: Squarementioning
confidence: 99%